The Effectiveness of mHealth in Improving Adherence to Antenatal Care Among Pregnant Women - Dewi Susanti (Yayasan Education and Social Center, 2024)
Antenatal care (ANC) is an essential service in an effort to improve maternal and infant health, but pregnant women's compliance with ANC visits is still a challenge in many countries, especially in areas with limited access to health services. The development of digital technology through mobile health (mHealth) offers innovative solutions to improve compliance through digital reminders, health education, and communication between pregnant women and health workers. This study aims to analyze the effectiveness of mHealth in improving antenatal care adherence in pregnant women through a systematic literature review approach. The study was conducted by examining ten relevant scientific articles from various academic databases, including systematic review, meta-analysis, scoping review, and implementation studies in various countries, including Indonesia. The results of the synthesis showed that mHealth interventions were consistently able to improve ANC visit adherence, both in the form of increasing the frequency of visits, the timeliness of examinations, and the continuity of pregnancy monitoring. SMS reminder-based interventions and mobile applications are the most dominant and effective forms, especially in the context of health services with limited access. This research confirms that mHealth has significant potential in supporting digital-based maternal health service transformation. The implications of these findings show the need to integrate mHealth technology in the primary health care system to improve the quality and coverage of antenatal care in a sustainable manner.